2013
DOI: 10.1089/met.2012.0183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Berberine Administration on Metabolic Syndrome, Insulin Sensitivity, and Insulin Secretion

Abstract: Administration of berberine leads to remission of metabolic syndrome and decreases in waist circumference, SBP, triglycerides, and total insulin secretion, with an increase in insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 14 publications
1
66
0
1
Order By: Relevance
“…In subjects with metabolic syndrome, BBR administration induces a 36% remission of the presence of metabolic syndrome, decreases waist circumference, systolic blood pressure, TG, glucose levels and insulin secretion, and increases insulin sensitivity [107]. BBR also reduces BMI, leptin levels and leptin/adiponectin ratio (Table 4), suggesting an adjustment of adipokine profile, as indicated by the in vitro finding that treatment of pre-adipocytes with BBR inhibits the differentiation to mature adipocytes as well as leptin and adiponectin expression and secretion [108].…”
Section: Bbr In the Treatment Of Diabetes And Metabolic Syndromementioning
confidence: 99%
“…In subjects with metabolic syndrome, BBR administration induces a 36% remission of the presence of metabolic syndrome, decreases waist circumference, systolic blood pressure, TG, glucose levels and insulin secretion, and increases insulin sensitivity [107]. BBR also reduces BMI, leptin levels and leptin/adiponectin ratio (Table 4), suggesting an adjustment of adipokine profile, as indicated by the in vitro finding that treatment of pre-adipocytes with BBR inhibits the differentiation to mature adipocytes as well as leptin and adiponectin expression and secretion [108].…”
Section: Bbr In the Treatment Of Diabetes And Metabolic Syndromementioning
confidence: 99%
“…Berberine is a natural isoquinoline alkaloid, which is present in medicinal herbs Coptidis rhizome (Huanglian in Chinese). Recent clinical studies have shown that berberine reduces blood pressure and increases systemic insulin sensitivity in patients with metabolic syndrome (Perez‐Rubio et al , ). Berberine has been shown to lower blood glucose and modulate lipid metabolism by activating AMP‐activated protein kinase (AMPK) (Ko et al , ; Chang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the low bioavailability [20] limited its wide use in clinical practice, berberine is already studied in a lot of clinical studies due to its various effects including lipid-lowering [21], changing the blood concentration of cyclosporin A in renal transplanted recipients [22], improving insulin resistance in type 2 diabetes mellitus patients [23,24], and ameliorating inflammation in patients with acute coronary syndrome [25]. Several studies have reported that berberine exerts its beneficial effects in diabetic nephropathy (DN) through the suppression of OS and ERS [26,27].…”
Section: Introductionmentioning
confidence: 99%